Impact of Burnout on Academic Performance and Well-Being among Medical Students: A Systematic Review: Impact of Burnout on Academic Performance and Well-Being among Medical Students - Imtiaz, Hajra; Ehsan, Muhammad Tauqeer; Hassan, Bilqis; Saleem, Sadaf; Khan, Fatima Muhammad; Fatima, Syeda Sanaa (Pakistan Journal of Health Sciences, 2026)
Medical student burnout has become a significant issue in the global community, with growing evidence of its negative implications on academic performance and mental health. Although there is an increasing body of research in this field, unified data on the extent and implications of burnout is scarce in the low- and middle-income contexts. Objective: To systematically review the impact of burnout on academic performance and well-being among undergraduate medical students. Methods: The systematic literature search was performed in PubMed, Scopus, Google Scholar, and Cochrane Library to identify research published from 2018 to 2024. Original English-language observational studies assessing burnout with validated measures and reporting academic or well-being outcomes were found. The selection of studies was done in accordance with PRISMA. The quality of methodology was determined with the help of the NIH Quality Assessment Tool. A narrative synthesis approach was used. Results: The qualitative synthesis included 15 studies. The prevalence of burnout was between 34.3% and 63.5. The most affected domain was emotional exhaustion. Increased burnout was always correlated to lower GPA/CGPA, worse examination results, lower learning motivation, worse quality of life, worse anxiety, depression, sleep problems, and stress. Conclusions: Burnout is highly prevalent among medical students and significantly compromises both academic performance and mental well-being. Institutional strategies focusing on workload regulation, mental health support, and improvement of learning environments are urgently needed.